Le Génie Féminin By Julia Kristeva’s Perspective In The Novel F? Qalb? Un?? ‘Ibriyah - Madawat Madawat M, Rabiatul; Udasmoro, Wening; Sukiman, Uki (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This research aims to explain the dimension of genius, which is a cutting-edge sector that sees the subjectivity of the female by Kristeva. The main character of the novel is named Nada. This research looks at how Nada has a level of intellect and freedom within her genius dimension. Kristeva shows the dimension of female genius itself through life and thinking skills. Nada can easily enter public spaces through the power of critical thinking. The method employed in this research is qualitative descriptive. The material object is the novel Fi Qalbi Unsä Ibriyah, which serves as the research data. The data source consists of texts that are primary data, comprising dialogues, descriptions, or actions in the novel regarding the characteristics of a female’s genius. This research is based on Julia Kristeva's theory of Le Génie Féminin. The results of the research show that everything in Nada and her actions is evidence of what Kristeva refers to as the dimension of female genius. The significance of Nada's genius lies more in action, life, and thoughts. As Kristeva thought, Nada is looking at evidence of female’s talent through three dimensions. Nada builds mechanisms through self-actualization by bodily speaking and acting. She let go of the stigma that had been attached to her family tradition for a long time. Therefore, the highlight noted researchers are not at the end of the story, but on the capabilities of females and the efficiency of females’ processes over their ideas and positions. Their abilities are what Kristeva terms a feminine genius. every woman exists within her own dimension of genius, as far as she is capable of challenging the sociohistorical conditions of identity (as a woman).